A RETROSPECTIVE EVALUATION OF TREATMENT STRATEGIES FOR UNSTABLE INTERTROCHANTERIC FEMORAL FRACTURES IN THE ELDERLY: COMPARING PROXIMAL FEMORAL NAIL ANTI-ROTATION VERSUS PRIMARY HIP HEMIARTHROPLASTY. - Chand, Subhash; Kumar, Naveen (Student's Journal of Health Research Africa, 2024)
Objectives The present investigation aims to contrast the outcomes of proximal femoral nail anti-rotation (PFNA) and primary hemiarthroplasty for treating unstable intertrochanteric femoral fractures in geriatric patients, focusing on functional outcomes, complication rates, and postoperative rehabilitation protocols. Methods The retrospective study, conducted at Pt. JLN Govt. Medical College, Chamba, Himachal Pradesh, contrasted the outcomes of proximal femoral nail anti-rotation (PFNA) and cemented hemiarthroplasty for unstable intertrochanteric femoral fractures (IFFs). Patients with American Society of Anesthesiologists (ASA) Grades II and III, aged over 65 years, in addition to having AO types A2 and A3 fractures were included in this study. Surgical procedures involved PFNA device insertion or hemiarthroplasty, followed by standardized post-operative protocols. Results The comparative analysis between the PFNA group (n = 50) and the Primary Hemiarthroplasty of the Hip (PHH) group (n = 43) revealed significant differences in treatment outcomes. Notably, the PFNA group exhibited a higher Harris Hip score at the 12-month follow-up (90.26 vs. 82.4, p = 0.016), with a larger proportion achieving excellent outcomes (36 vs. 23). Moreover, secondary outcomes, including surgical time, intra-operative blood loss, post-operative hemoglobin levels, and duration of hospital stay, favored the PFNA group, showing statistically significant differences (p < 0.00001, except for perioperative blood transfusions, p = 0.00536). Conclusion The findings of the investigation implied that PFNA fixation gives rise to superior clinical outcomes when compared to PHH for unstable intertrochanteric femoral fractures. This has been proven by the identification of better functional scores and reduced post-operative complications in the case of patients treated with PFNA. Recommendation The study recommends prioritizing PFNA fixation over primary hemiarthroplasty for unstable intertrochanteric femoral fractures based on superior functional outcomes and fewer post-operative complications.